BUKA LUWUR TRADITION: PORTRAIT OF LIVING HADITH AT HAUL SUNAN KUDUS - Arif Friyadi (Nabawi)
Living hadith is the response of certain Muslim communities in applying the words that come directly from the Prophet Muhammad. This response occurs both in the form of personal and community in interpreting certain hadiths. This research will discuss the tradition of Buka Luwur with portraits of living hadiths on the haul of Sunan Kudus. This library research uses interview techniques and field observations to observe the Buka Luwur phenomenon in the Haul Sunan Kudus Commemoration. This social phenomenon is categorized as living hadith because there are several indications, including; First, this tradition was inspired by the turn of the kiswah of the Kaaba. Second, this tradition is considered by the Kudus community as a tribute to the services of Islamic preachers in the holy city, namely Sayyid Ja'far Sadiq, Sunan Kudus. Third, this tradition is considered to be based on hadith. The existence of this tradition also means that Islam does not only come as an emphasis on sharia, but also accommodates local traditions. From this phenomenon emerged a strong Islamic motivation in the form of generosity and inner satisfaction with respect to the first Islamic propagator on the island of Java.